Rb function in extraembryonic lineages suppresses apoptosis in the CNS of Rb-deficient mice - de Bruin, Alain (National Academy of Sciences, 2003)
Retinoblastoma (Rb)-deficient embryos show severe defects in neurogenesis, erythropoiesis, and lens development and die at embryonic day 14.5. Our recent results demonstrated a drastic disorganization of the labyrinth layer in the placenta of Rb-deficient embryos, accompanied by reduced placental transport function. When these Rb(-)(/)(-) embryos were supplied with a wild-type placenta by using either tetraploid aggregation or genetic approaches, animals survived until birth. Here we analyze the role of extraembryonic Rb in regulating proliferation, apoptosis, and differentiation in the rescued animals at different developmental stages. Many of the neurological and erythroid abnormalities thought to be responsible for the embryonic lethality of Rb(-)(/)(-) animals, including the ectopic apoptosis in the CNS, were virtually absent in rescued Rb(-)(/)(-) pups. However, rescued animals died at birth with severe skeletal muscle defects. Like in Rb knockout embryos, rescued animals showed a marked increase in DNA replication and cell division in the CNS. In sharp contrast, the typical widespread neuronal apoptosis was absent in Rb-deficient embryos reconstituted with a normal placenta. In lens fiber cells, however, the inappropriate proliferation and apoptosis that is normally observed in Rb(-)(/)(-) embryos continued unabated in rescued animals. These results demonstrate that Rb function in extraembryonic lineages plays an important role in the survival of neuronal cells and in the differentiation of the erythroid lineage, providing mechanistic insight into the cell autonomous and nonautonomous functions of Rb during development.